Anatomical and Morphological Variability of Leaves, Stem, and Root Among Eddoe Taro (Colacasia esculenta var Esculenta) - Lutfy Ditya Cahyanti; Mahmudah Hamawi; Use Etica; Jamilah Mohd Salimaa (PLANTA TROPIKA, 2025)
Colocasia esculenta (taro) is a significant staple crop cultivated for its edible corms, roots, and leaves. Despite its agricultural importance, limited anatomical studies have focused on the vegetative organs (leaf, stem, and root) of various taro cultivars. This study aimed to describe and compare the anatomical structures of leaves, stems, and roots among six taro cultivars (Jepang putih, Jepang merah, Gambir, Semir, Ketan, and Sutra). The six cultivars were cultivated using sucker propagation in three replicated blocks. Parameters assessed included leaf, stem, root anatomy, chlorophyll content (a, b, and total), stomata characteristics, epidermal cell number and length, and root tissue thickness (epidermis, endodermis, cortex, and stele). Significant anatomical differences were found among the cultivars. The Gambir cultivar resulted in the highest chlorophyll a, b, and total chlorophyll content. Jepang merah had the thickest root epidermis and cortex, Gambir had the thickest endodermis, and Semir showed the thickest stele. Ketan cultivar had the highest number of stomata and epidermal cells. Anatomical variation exists among the six cultivars of Colocasia esculenta studied, indicating potential for cultivar-specific functional adaptations. These findings may contribute to cultivar selection and improvement for various agricultural and nutritional purposes.